Antegrade rheolytic thrombectomy and thrombolysis for superior sagittal sinus thrombosis using burr hole access. (3rd April 2014) - Lee, Darrin J; Latchaw, Richard E; Dahlin, Brian C; Dong, Paul R; Verro, Piero; Muizelaar, J Paul; Shahlaie, Kiarash
Abstract : Superior sagittal sinus (SSS) thrombosis has high morbidity and mortality, and urgent recanalization is critical for severe cases. Standard endovascular techniques for thrombolysis and thrombectomy use retrograde venous access, an approach that may be unsuccessful in cases with extensive firm clot burden involving the dural sinuses distal to the SSS. An anterior open transcranial approach to the SSS for catheter sheath placement to facilitate antegrade mechanical thrombectomy and thrombolysis of the SSS and more distal sinuses has not been previously described. Here we describe a case in which multiple unsuccessful attempts at retrograde endovascular access were attempted. Thus, a burr hole over the anterior SSS was performed for daily endovascular antegrade procedures using the Angiojet rheolytic catheter device and chemical thrombolysis. Near-complete recanalization of the SSS was achieved with venous outflow via dilated left transverse and left sigmoid sinuses, along with significant collateral flow in multiple cerebral veins.